Aquifer systems management [electronic resource] : Darcy's legacy in a world of impending water shortage - Chery, Laurence; Darcy, Henry , 1803-1858; Marsily, Ghislain de (International Association of Hydrogeologists selected papers, 2007)
A collection of papers from the International Association of Hydrogeologists, Dijon 2006, divided into six themes: large aquifers, resource assessment; large aquifers, water salinity and evolution;